A Numerical Study on Combustion and Emission Characteristics of a Medium-Speed Diesel Engine Using In-Cylinder Cleaning Technologies - Shuang He; Bao-Guo Du; Li-Yan Feng; Yao Fu; Jing-Chen Cui; Wu-Qiang Long (Energies, 2015)
In order to clarify the potential of internal purification methods on medium speed diesel engines to meet the IMO Tier III nitrogen oxide (NOx) emission regulations, combined 1-D engine working cycle simulation and 3-D CFD simulation were conducted to predict the performance and emissions of the engine under different valve close timings, geometric compression ratios, injection timings, and Exhaust Gas Recirculation (EGR) rates. The numerical results show that, as the inlet valve close timing is advanced, NOx is reduced by as much as 27%, but the peak of premixed combustion heat release rate is increased; this can weaken the ability to reduce NOx with the Miller cycle. Moreover, the peak of premixed combustion heat release rate is reduced when the geometric compression ratio is increased to 15.4, and linking with injection timing by delaying 6°CA can further reduce NOx by 55.3% from the baseline. Finally, over 80% NOx reduction can be achieved when the above schemes are combined with over 15% EGR. The NOx and soot can be reduced simultaneously by using moderate Miller cycle combination with moderate EGR, and the results show a large reduction of NOx and moderate reduction of soot. This can be a feasible technical solution to meet Tier III regulations.